Different configurations of humidification-dehumidification desalination systems: Thermal and economic assessment. (15th April 2022) - Khass, Tarek M.; Mohammed, Ramy H.; Qasem, Naef A.A.; Zubair, Syed M.
Highlights: Thermoeconomic performance of various HDH configurations is compared. Single, double, and triple humidifiers are examined and contrasted. The effectiveness of humidifiers and dehumidifiers influences freshwater production. The water-heated multi-humidifier HDH cycle generates more freshwater. A double humidifier air-heated HDH cycle generates fresh water at 2.06 $/m 3 . Abstract: Drought has hit several water-stressed regions, with serious consequences for water and food security. In this regard, the low-cost and low-grade thermally driven humidification-dehumidification desalination cycle has good potential to provide freshwater in arid regions. From energy and economic point of view, different configurations of the humidification-dehumidification cycle have been proposed in the literature without a comprehensive comparison to identify the most suitable one. Thus, this paper investigates the thermal and economic performance of several multi-humidifier water- and air-heated humidification-dehumidification cycles. Thermodynamic models are structured to study the behavior of each cycle. The models rely on heat and mass transfer balances for each component. The effectiveness method is implemented for humidifiers and dehumidifiers to evaluate heat and mass exchangers. The models are validated using previously published data. The series seawater flow, triple humidifier, water-heated humidification-dehumidification cycle could deliver 151.2 kg/h of fresh water at a maximum temperature of 70 °C, with a gain output ratio of 1.995 and a specific cost of 2.73 $/m 3 . This cost rises by around 16% when a maximum temperature of 60 °C is employed. Results reveal that using a double-humidifier in an air-heated humidification-dehumidification cycle produces freshwater of 102.2 kg/h at the lowest price of $2.06/m 3 . It is concluded that the multi-humidifier water-heated humidification-dehumidification cycle produces more freshwater and less gain output ratio than the multi-humidifier air-heated humidification-dehumidification cycle.